A VIEW ON EXPERIENCE AND COMMUNICATION PERSPECTIVES IN LUNG CANCER PATIENTS IN CROATIA (Zdravstveni glasnik, 2024)
Introduction: Well-balanced communication between healthcare professionals and oncology patients is the first step toward goals of caring for patients.Aims: In constant aim to improve patient outcomes, we aspired to uncover shortcomings in communication between healthcare professionals and patients suffering from lung cancer. An online survey of a non-probabilistic sample of cancer patients from twelve countries of Central and Eastern Europe designed and implemented by the Croatian Coalition of Associations in Healthcare.Methods: 472 lung cancer subjects were selected from the sample of results from 2,460 Croatian participants in the study from Oct. 2018. to Feb. 2019. Participants’ sociodemographic and clinical characteristics, experience and communication with healthcare professionals, key areas of inefficiency, psychological and social support were assessed. The analysis included descriptive statistics and chi square to assess demographic differences.Results: The study revealed four main results: (i) only a minority of the participants were satisfied with the communication process, (ii) majority were not told that they could bring family member during delivering bad news, (iii) there was a clear unmet need to have a discussion on the impact of cancer on day to day activities (iv) participants’ preferences indicate that the greatest improvement would be to perform all services at one place.Conclusions: This study revealed that one of the leading problems in oncology care according to patients is the lack of education and effective communication. Based on the obtained data, we conclude that there is a large space for improvement in patient experience and communication.